Chapter I disegni leonardiani di architettura del Ms. B: metodologia di ricerca storica applicata al processo ricostruttivo 3D - Smalzi, Daniela (Territori, 2023)
The use of 3D modelling in practices of valorisation and dissemination of historic-architectural knowledge and restoration is now consolidated. Virtual models must, however, match principles of scientific rigour, comprehensibility and evaluability by the users, as stated in the London Charter and in the Seville Principles. This paper aims at presenting the methodology used in the virtual reconstruction of some drawings by Leonardo da Vinci, developed to ensure the correct dissemination of the historical contents delivered through the drafting of a 'traceability card' compliant with the international Charters principles.